Digital fluency - Jeevan Pinto; Santhosh B; PINTO (Jeevan); SANTHOSH (B) (Mangaluru United Agencies, 2022)
Digital Fluency it is a compulsory subject for all UG courses as per new National Education Policy (NEP). This book has been structured to help the undergraduate students of BA, BSW, BHS, BCom, BSc BBA etc,. The book gets to the heart of digital buzzwords and concepts, and tells what they truly mean. The book contains the understandable explanation of concepts of new technologies such as Artificial intelligence, Machine Learning, Deep Learning, Database Management for Data Science, Big Data Analytics, Internet of things (IOT) and Industrial Internet of Things (IIOT), coud computing and its service models, cyber security and Types of cyber-attack.
Keywords: Cloud Computing; Artificial Intelligence; Cyber Security; I Semester; NEP